If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + x * x = 4 + -1(x + 2)(3 + -1x) Reorder the terms: 2(-4 + x) + x * x = 4 + -1(x + 2)(3 + -1x) (-4 * 2 + x * 2) + x * x = 4 + -1(x + 2)(3 + -1x) (-8 + 2x) + x * x = 4 + -1(x + 2)(3 + -1x) Multiply x * x -8 + 2x + x2 = 4 + -1(x + 2)(3 + -1x) Reorder the terms: -8 + 2x + x2 = 4 + -1(2 + x)(3 + -1x) Multiply (2 + x) * (3 + -1x) -8 + 2x + x2 = 4 + -1(2(3 + -1x) + x(3 + -1x)) -8 + 2x + x2 = 4 + -1((3 * 2 + -1x * 2) + x(3 + -1x)) -8 + 2x + x2 = 4 + -1((6 + -2x) + x(3 + -1x)) -8 + 2x + x2 = 4 + -1(6 + -2x + (3 * x + -1x * x)) -8 + 2x + x2 = 4 + -1(6 + -2x + (3x + -1x2)) Combine like terms: -2x + 3x = 1x -8 + 2x + x2 = 4 + -1(6 + 1x + -1x2) -8 + 2x + x2 = 4 + (6 * -1 + 1x * -1 + -1x2 * -1) -8 + 2x + x2 = 4 + (-6 + -1x + 1x2) Combine like terms: 4 + -6 = -2 -8 + 2x + x2 = -2 + -1x + 1x2 Solving -8 + 2x + x2 = -2 + -1x + 1x2 Solving for variable 'x'. Reorder the terms: -8 + 2 + 2x + x + x2 + -1x2 = -2 + -1x + 1x2 + 2 + x + -1x2 Combine like terms: -8 + 2 = -6 -6 + 2x + x + x2 + -1x2 = -2 + -1x + 1x2 + 2 + x + -1x2 Combine like terms: 2x + x = 3x -6 + 3x + x2 + -1x2 = -2 + -1x + 1x2 + 2 + x + -1x2 Combine like terms: x2 + -1x2 = 0 -6 + 3x + 0 = -2 + -1x + 1x2 + 2 + x + -1x2 -6 + 3x = -2 + -1x + 1x2 + 2 + x + -1x2 Reorder the terms: -6 + 3x = -2 + 2 + -1x + x + 1x2 + -1x2 Combine like terms: -2 + 2 = 0 -6 + 3x = 0 + -1x + x + 1x2 + -1x2 -6 + 3x = -1x + x + 1x2 + -1x2 Combine like terms: -1x + x = 0 -6 + 3x = 0 + 1x2 + -1x2 -6 + 3x = 1x2 + -1x2 Combine like terms: 1x2 + -1x2 = 0 -6 + 3x = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-2 + x) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Solution
x = {2}
| y+2(y-8)= | | 29/66/e^50 | | (X+4)(x-15)-6x=0 | | 15+18-16=13 | | 2x^4=9x^2 | | 5y-8x-10=0 | | e^50*k=29/66 | | (2y-6)+(30)+(x)=180 | | (x-8)2=0 | | (-3/4)/(-5/6) | | -3x-2(-7x-4)=74 | | 13=-4(x+8)+5x | | (7t-2)-(-3t+1)=(1-3t) | | -9/-5= | | 5-3(2h+6)=7+5h | | (4x-3)(8x+4)=0 | | 3(x+2)+3x+1=2(x-1)-7 | | 11/28=4/x | | 12x^3-3x^2=0 | | 3.5/x=11/28 | | 55x-12=x-24 | | 59+1.75x=39.99+2.50x | | x(1M)+(-2N)=0 | | 2/3x2-5= | | 3p+6=78 | | 2/3x-5=-2 | | C(t)=2x+180 | | 5x-5y+7a= | | 3=-3/2(x+6) | | Ic(t)=2x+180 | | 16=4(2x+1) | | x-1/2=1/4 |